Enhancing Inventory Management in Dental Clinics through Agile Methodology: A Practical Approach - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research investigates complex inventory management issues in dental clinic settings, including lack of transparency in stock monitoring, challenges in timely procurement planning, and the risk of losing information about expiration dates or item conditions. The methods employed include an initial analysis of existing inventory management processes, stakeholder interviews within dental clinics, and functional testing and user acceptance analysis of the developed inventory system. The research findings demonstrate that developing inventory systems using Agile methodology can address various challenges in dental clinic inventory management, yielding satisfactory results in functional testing and high user acceptance rates. The contribution of this research lies in providing practical concepts and guidelines for dental clinics to manage inventories more efficiently and adaptively, as well as laying a solid foundation for developing inventory systems responsive to changing needs and fast-paced market dynamics.